2017
DOI: 10.5194/amt-10-221-2017
|View full text |Cite
|
Sign up to set email alerts
|

Observing relationships between lightning and cloud profiles by means of a satellite-borne cloud radar

Abstract: Abstract. Cloud electrification and related lightning activity in thunderstorms have their origin in the charge separation and resulting distribution of charged iced particles within the cloud. So far, the ice distribution within convective clouds has been investigated mainly by means of ground-based meteorological radars. In this paper we show how the products from Cloud Profiling Radar (CPR) on board CloudSat, a polar satellite of NASA's Earth System Science Pathfinder (ESSP), can be used to obtain informati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…Lightning rates also show a positive correlation with mass eruption rate and plume height [Van Eaton et al 2016;Prata et al 2020;Smith et al 2021;Van Eaton et al 2022]. These studies parallel existing meteorological models that indicate the importance of ice and strong updrafts for lightning activity in regular thunderstorms [Williams et al 1989;Saunders et al 2006;Deierling et al 2008;Buiat et al 2017;Schultz et al 2017]. Several papers, including those examining the eruptions of Kelud, Indonesia [Hargie et al 2019], Calbuco, Chile [Van Eaton et al 2016], Redoubt, USA [Behnke et al 2013], and Bogoslof, USA [Smith et al 2018; volcanoes, have also examined general spatial trends of globally detected lightning locations.…”
Section: Introductionsupporting
confidence: 53%
“…Lightning rates also show a positive correlation with mass eruption rate and plume height [Van Eaton et al 2016;Prata et al 2020;Smith et al 2021;Van Eaton et al 2022]. These studies parallel existing meteorological models that indicate the importance of ice and strong updrafts for lightning activity in regular thunderstorms [Williams et al 1989;Saunders et al 2006;Deierling et al 2008;Buiat et al 2017;Schultz et al 2017]. Several papers, including those examining the eruptions of Kelud, Indonesia [Hargie et al 2019], Calbuco, Chile [Van Eaton et al 2016], Redoubt, USA [Behnke et al 2013], and Bogoslof, USA [Smith et al 2018; volcanoes, have also examined general spatial trends of globally detected lightning locations.…”
Section: Introductionsupporting
confidence: 53%
“…As in Hokuriku winter clouds, graupel and ice crystals have been found to be critically important in the electrification of many cloud systems globally, including summer thunderstorms (Buiat et al, 2017;Carey & Rutledge, 2000;Deierling et al, 2008).…”
Section: Model Of Hokuriku Winter Thunderstormsmentioning
confidence: 99%
“…Another study, by Carey and Rutledge (2000), reported on a tropical convective complex over the Tiwi Islands on 28 November 1995, observed by a C-band polarimetric radar. It is noteworthy that in its initial phase the storm was dominated by warm rain processes.…”
Section: Introductionmentioning
confidence: 99%